Estrutura e produção de serapilheira de floresta de mangue na região estuarina-lagunar do baixo São Francisco sergipano - Menezes, Luciano Carlos Sobral de (2010)
The watershed of São Francisco River has suffered drastic degradation processes, with emphasis on the environmental damages created in the lower São Francisco. The river estuary has very extended mangrove areas threatened by human actions such as shrimp farming and the removal of timber to be used in construction. The characteristics of mangrove areas at the mouth of the river have not been enough studied mostly from changes occurred in the last two decades. The structural behavior of mangrove forests is a response to environmental conditions and greater structural development is related to subsidies of rainfall and tidal near the equatorial zones, under the influence of the intense convective activity of the intertropical convergence zone. This zone, in general, includes latitudes between 10 ° and 15 ° from the Equator. The structure of the forest is defined based on various parameters, such as species composition, diameter at breast height (1.30 m substrate), height, basal area, density, spatial distribution and distribution by class of diameter, and spatial patterns of species distribution. Significant amount of nutrients can return to the soil through the decomposition of leaves, stems, fruits, flowers and animal remains and fecal material, components that defines litterfall or litter, and is a parameter frequently used to evaluate the ecosystems productivity. The objective of this work was to evaluate the structural behavior of the mangrove litter production and estuarine river San Francisco.